Bariery dla innowacji i transferu techniki w Polsce oraz sposoby ich pokonywania - Filip Tużnik (Studia i Materiały)
One of the main determinants of companies’ market rating is their innovative activity. Though, many managers must cope with barriers they encounter while implementing new technolo- gies. The effectiveness in overcoming barriers could have an influence on company’s success and development of the national economy. This article focuses on classification of the main barriers that appear during innovative activity and the technology transfer process. There are three groups of barriers taken into consideration: these of financial origin, these arising between business and science, and those of legal origin. One can also find suggestions how to overcome barriers, given by domestic experts and entrepreneurs.